STRESS AND COPING MECHANISM TOWARDS MENSTRUAL CYCLE DISORDER TO TEENAGER GIRL - Mesarini, Bisma Ayu; Astuti, Vitaria Wahyu (Jurnal Penelitian STIKES Kediri, 2013)
Everyone has experienced stress and become motivated to do coping mechanism. The purpose of this study to analyze the relationship between stress and coping mechanisms of the menstrual cycle disorders. The design used was cross sectional. The populations were grade IV student at STIKES RS Baptis Kediri. The samples were 35 respondents using purposive sampling. The independent variable was coping mechanism. The dependent variable was level of stress towards period disorders. Data were collected through questionnaires and observation. The analysis using "logistic regression" tests with significance level a ≤ 0.05 the result P=0.767 it means between levels of stress and coping mechanisms are not related, for the stress levels with menstrual cycle disorders obtained P=0.018 there is a relationship the level of stress and menstrual cycle disorders. The conclusion, the coping mechanisms not related to the level of stress but the stress levels related to menstrual cycle disorders for student grade IV at STIKES RS. Baptis Kediri.